Towards inclusive food systems: Pandemics, vulnerable groups, and the role of social protection - Kumar, Neha (2021)
Neha Kumar GLOBAL FOOD POLICY REPORT Rwanda Discussion of IFPRI’s 2021 Global Food Policy Report: Transforming Food Systems After COVID-19 Rwanda Strategy Support Program (Rwanda SSP) APR 28, 2021 - 09:00 AM TO 10:30 AM EDT